Policy and Strategy for Patriotism, Institutions and Economic Development in Nigeria - Onyeisi, Ogbonna (Enugu, Nigeria, 2019)
The book is an outcome of the author's personal research work during Senior Executive Course, No. 35 of the National Institute for Policy and Stategic Studies, Kuru, Jos, Nigeria. The book outlined the lucid ways and means of achieving economic development, through promotion of patriotism and strengthening of institutions.
Includes bibliographical references, index
osc 25/04/23
Loans
Keywords: Economic development - policy; Nigeria